2012
DOI: 10.3892/or.2012.1740
|View full text |Cite
|
Sign up to set email alerts
|

Role of systemic chemotherapy in the management of resected or resectable colorectal liver metastases: a systematic review and meta-analysis of randomized controlled trials

Abstract: Abstract. Liver metastases are a common event in patients with colorectal cancer. Surgical resection, if feasible, produces a survival benefit. We performed a systematic review of randomized clinical trials (RCT) and meta-analysis to address the question if current available studies support the use of systemic chemotherapy as an adjunct to surgery in resected/ resectable patients. The search was based on major databases (PubMed, CancerLit, Embase, Medscape and Cochrane) of published literature and selecting ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…The exact timing of chemotherapy treatment still remains uncertain today; recently 2 interesting meta-analyses of randomized clinical trials [10], [11] have been published in which patients with a colorectal tumor with synchronous resectable liver metastases were treated with perioperative chemotherapy (neoadjuvant and/or adjuvant) with an improvement statistically significant in terms of progression-free survival or disease-free survival. Unfortunately, both studies did not demonstrate an improvement in overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…The exact timing of chemotherapy treatment still remains uncertain today; recently 2 interesting meta-analyses of randomized clinical trials [10], [11] have been published in which patients with a colorectal tumor with synchronous resectable liver metastases were treated with perioperative chemotherapy (neoadjuvant and/or adjuvant) with an improvement statistically significant in terms of progression-free survival or disease-free survival. Unfortunately, both studies did not demonstrate an improvement in overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that adjuvant SCT reduced both long- and short-term mortality after resection of resected HMCRC by approximately twice that suggested in the previous study. 33 A subsequent traditional meta-analysis in 2012 35 concluded that there was a trend advantage of SCT combined with surgical resection of colorectal liver metastases compared with surgery alone (pooled HR 0.743; CI 0.527–1.045; P = 0.088), but failed to reach statistical significance. The results of our meta-analysis are consistent with the results from this previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate timing of CRS and systemic therapy is also important for these patients. At this time, neoadjuvant chemotherapy for resectable HM [ 16 , 17 ] or PC [ 18 , 19 ] from CRC has demonstrated mixed results in the literature. Determination of optimal timing of treatment should be made based on a multidisciplinary approach, particularly in cases of resectable synchronous HM, PC, and pulmonary metastasis of CRC origin.…”
Section: Discussionmentioning
confidence: 99%